AI based comparison of prefrontal cortex activity between piano-majors and non-piano-major musicians during score-based playing and Motif-improvisation - Hyo Jee Kang; Su-cheon Lee; Yoobin Hwang; Jisun Ham; Manbok Park; Kang-moon Park (PLoS ONE, 2025)
This study aimed to investigate how neural activation patterns differ between pianists and non-pianist musicians during piano performance tasks, using an LSTM-Autoencoder model applied to fNIRS data. A total of 22 participants, comprising both piano-majors and non-piano-majors, were involved in this study. Each participant’s performance data, collected during Score-based playing and improvisation tasks, was analyzed using a Long Short-Term Memory (LSTM) Autoencoder model. Reconstruction errors in specific brain channels, measured through Functional Near-Infrared Spectroscopy (fNIRS), showed group-level patterns—particularly in channels 1 and 15 (app. BA 45L, BA 45R)—but these differences did not reach statistical significance in inferential tests. These findings are therefore reported as exploratory and suggest distinct neural engagement patterns associated with varying levels of musical expertise.